Accesibilidad al examen de papanicolaum en las trabajadoras del mayorista de la ciudad de Ibarra 2025 - Maldonado Espinosa, Patricia Esperanza (2025)
This study aimed to develop educational strategies to improve access to PAP among female workers at the Ibarra Wholesale Market in 2025. A quantitative methodology was used, with a non-experimental, descriptive and cross-sectional design. For this study, a non-probability convenience sample was used, selecting 90 female workers from the wholesale market in the city of Ibarra, who met the established inclusion criteria. The results showed that, among women aged 18 to 25, 82% reported lack of knowledge about the usefulness of PAP smears, while 65% of those with only secondary education reported having received no preventive information. Likewise, 38% identified fear, shame and misinformation as main barriers, and 70% reported negative experiences with the PAP. It was concluded that lack of information, limited physical access, and unfavorable experiences with health personnel were key barriers affecting PAP coverage. Educational strategies focused on health promotion and disease prevention were an effective way to raise awareness among female workers and encourage their participation in timely screening programs.